A message from the Coalition of Women Delegates (1976)
This flyer from the Democratic Task Force and Democratic Women's Agenda '76 urges delegates to support equal participation of women in the Democratic Party, highlighting that despite past reforms, women made up only one-third of convention participants in 1976. It calls for backing the Rules Committee Minority Report, which would require equal representation of men and women at the 1980 Convention. The document frames this vote as a crucial step toward greater female participation in party leadership, commissions, and government positions.